Analysing Digital Transformation in Indonesia: the Government's Role in Improving Public Services for Economic Activity - luis armando sabarofek; Achmad Nurmandi; Muhammad Younus (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
This study examines the strategic role of the Indonesian government in promoting digital transformation as a key instrument for improving public services and supporting economic activities. While previous studies have widely discussed digital transformation from technological and administrative efficiency perspectives, limited attention has been given to its direct impact on community-based economic activities. Addressing this gap, the study aims to analyze government digital policy strategies, evaluate the implementation of digital public services, and assess their contribution to creating a more inclusive and responsive economic environment. A qualitative descriptive-analytical approach is employed, supported by bibliometric analysis using secondary data from the Scopus database. Documents published between 2015 and 2025 were analyzed using RStudio to identify publication trends, dominant themes, and knowledge structures related to digital transformation in the public sector. The findings reveal a significant increase in global research on digital transformation, with an annual growth rate, indicating its growing relevance in governance and economic development. Digital transformation is found to represent a structural shift in public service delivery rather than merely technological adoption. In Indonesia, government-led digital initiatives have improved bureaucratic efficiency, expanded market access, and supported the growth of digital economic actors, particularly MSMEs and startups. This study concludes that digital transformation plays a crucial role in strengthening public service performance and accelerating inclusive economic growth. The findings provide theoretical contributions to digital governance literature and practical insights for evidence-based policymaking in Indonesia.